2016
DOI: 10.1182/blood-2016-05-715292
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin modulation is associated with improved homing and engraftment after umbilical cord blood transplantation

Abstract: • EPO-EPOR signaling reduces UCB CD34 1 HSPC engraftment through inhibition of BM homing and enhancement of erythroid differentiation.• When used in clinical UCB transplantation, HBO therapy is safe and reduces EPO serum levels, potentially improving blood count recovery.Umbilical cord blood (UCB) engraftment is in part limited by graft cell dose, generally one log less than that of bone marrow (BM)/peripheral blood (PB) cell grafts. This migratory inhibitory effect was reversed by depleting EPOR expression on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 22 publications
3
40
0
Order By: Relevance
“…Our findings support a new role for EPO in UCB HSPC differentiation and BM homing, processes that dictate subsequent engraftment outcomes [9]. Approximately 20% of UCB HSPCs express EPOR [9]. Exposing UCB HSPCs to EPO reduced the percentage of UCB HSPCs migrating toward stromal derived factor-1 (SDF-1/CXCL12, a chemokine that mediates HSPC homing to the marrow [5]), an effect reversed by treating the cells with EPO-or EPOR-neutralizing antibodies or by depleting EPOR on HSPC.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…Our findings support a new role for EPO in UCB HSPC differentiation and BM homing, processes that dictate subsequent engraftment outcomes [9]. Approximately 20% of UCB HSPCs express EPOR [9]. Exposing UCB HSPCs to EPO reduced the percentage of UCB HSPCs migrating toward stromal derived factor-1 (SDF-1/CXCL12, a chemokine that mediates HSPC homing to the marrow [5]), an effect reversed by treating the cells with EPO-or EPOR-neutralizing antibodies or by depleting EPOR on HSPC.…”
supporting
confidence: 73%
“…Our findings support a new role for EPO in UCB HSPC differentiation and BM homing, processes that dictate subsequent engraftment outcomes [9]. Approximately 20% of UCB HSPCs express EPOR [9].…”
supporting
confidence: 69%
See 1 more Smart Citation
“…He and his colleagues followed up with a phase 1 pilot study of 15 patients with cancer who received cord blood transplantation after undergoing chemotherapy and radiotherapy to kill off their own bone marrow. Dr. Aljitawi found that exposing them to hyperbaric conditions, using pure oxygen under higher atmospheric pressure, safely reduced their erythropoietin levels . For 48 control patients who received transplantations but no hyperbaric treatment, engraftment required an average of 20.5 days.…”
Section: Gearing Up For Improved Engraftmentmentioning
confidence: 99%
“…This includes the roles of glucocorticosteroids , inhibitors of histone deacetylase (HDAC) 5 , inhibitors of DPP4 in vitro and in vivo in patients using the FDA‐approved orally active DPP4‐inhibitor sitagliptin , combinations of a DPP4 inhibitor plus prostaglandin (PG)E , and short‐term exposure of cells to mild heat (39°C) exposure . Treatment of recipients undergoing CB HCT has also used hyperbaric chambers . All of the above‐described laboratory/clinical procedures, as well as those noted in my reviews , can be used alone to enhance preclinical/clinical CB HCT of human cells, but there is no reason that they cannot also be used in combination in sequence as noted in Figure , efforts currently ongoing in the laboratory, to see if such sequential combinations can more effectively enhance the efficacy of the CB cells for HCT than each single procedure.…”
mentioning
confidence: 99%